Physical therapy rehabilitation of Cohen syndrome in Pakistan - Saleem, Safa; Sarmad, Samia; Jawad, Muhammad; Liaqat, Sameed; Ahad, Muhammad; Rauf, Wardah (Journal of the Pakistan Medical Association, 2025)
Cohen Syndrome is a rare genetic disorder. It is caused by the mutation of VPS13b gene which is present on chromosome number 8. It was first described in 1973. Here is a case report of a male child who presented to Paediatric Physical Therapy and Neuro Rehabilitation Department of The University of Lahore Teaching Hospital, Lahore, on July 25, 2021, with developmental delay due to hypotonia, typical facial gestalt, neutropenia, intellectual disability and speech delay. His genetic testing confirmed the diagnosis of Cohen syndrome. He received an intensive and holistic physical therapy programme for 3 years (July 2021 till July 2024) which helped him reach his developmental milestones. This study shows that with efficient goal setting, early intervention along with enriched environment and family centred approach can help the child achieve age-appropriate milestones. Keywords: Cohen syndrome, Physical therapy, Genetic diseases.